POCOP-Ni(II) pincer compounds derived from phloroglucinol. Cytotoxic and antioxidant evaluation - Amaya-Flórez, Andrés; Serrano-García, Juan S.; Ruiz-Galindo, Jordi; Arenaza-Corona, Antonino; Cruz-Navarro, J. Antonio; Orjuela, Adrian L.; Alí-Torres, Jorge; Flores-Alamo, Marcos; Cano-Sanchez, Patricia; Reyes-Márquez, Viviana; Morales-Morales, David (Frontiers in Chemistry, 2024)
POCOP-Ni(II) pincer compounds have primarily been explored as catalysts, but their potential biological activity has been scarcely studied. To address this gap, we evaluated the anticancer and antioxidant potential of four POCOP-Ni(II) complexes derived from phloroglucinol. A comprehensive supramolecular analysis, based on single-crystal X-ray diffraction (DRX) structures, was conducted using Hirshfeld surfaces and non-covalent interaction analysis. The cytotoxicity of all complexes was systematically assessed against various cancerous cell lines, as well as a noncancerous cell line (COS-7). The results revealed that complexes 1b and 1c exhibited remarkable antiproliferative activity, with IC50 values ranging from 2.43 to 7.85 μM against cancerous cell lines U251, K562, HCT-15, MCF-7, and SKLU-1. To further elucidate their mechanism of action, a competitive fluorescence displacement assay with ethidium bromide (EB) suggested that these complexes possess the ability to intercalate with DNA. This multifaceted investigation not only enhances our understanding of the biological potential of POCOP-Ni complexes but also provides valuable insights into their structural features and interactions, paving the way for future exploration in both catalytic and therapeutic domains.